Monte Carlo simulation in communication system / Mazlina Poniran - Poniran, Mazlina (2009)
In this research, Monte Carlo simulations were used to evaluate the bit error rate (BER) due to the degrading effects in a communication system. The communication system under study consists of a binary PSK modulator/demodulator with both signal points in the signal constellation lying in the direct (in-phase) channel. The filter at the output of the modulator is a third-order Butterworth filter with a bandwidth equal to the bit rate ( BW = rb ), leads to intersymbol interference (ISI). Simulation results were compared with the ideal ( zero ISI ) result in order to determine the increase in BER resulting from the filter - induced ISI. The evaluations demonstrate that the increase in the BER resulting from the ISI caused by the filter is evident.